Analisis Penerapan Sistem Informasi Akuntansi Dan Kualitas Laporan Keuangan UMKM Dalam Mengembangkan Bisnis Di Kota Batam: Penerapan Sistem Informasi Akuntansi; Kualitas Laporan Keuangan UMKM; Dalam Mengembangkan Bisnis - Syahril Effendi; Baru Harahap (JURNAL AKUNTANSI BARELANG, 2019)
This research is motivated by the number of companies in Batam that closed and left Batam which caused many unemployment, so the role of MSMEs in Batam is now very much needed. The focus of this study is to determine the application of accounting information systems and the quality of MSME financial reports on business development in Batam City. This research was conducted at Micro, Small and Medium Enterprises (SMEs) in Batam City, Riau Islands Province. The subjects of this study are business people or MSME businesses that utilize revolving funds from the City Government (Pemko) of Batam, which are recorded at the Batam City Cooperative and MSME Office. The population in this study are business or MSME businesses that utilize revolving funds from the City Government (Pemko) of Batam as many as 2,105 businesses and by using the Slovin formula so that the sample becomes 96 MSMEs. All samples come from SMEs who run businesses in Batam City. Research shows that the application of accounting information systems has a significant effect on business development in Batam City, the quality of MSME financial reports has a significant effect on business development in Batam City, the application of accounting information systems and the quality of MSME financial reports simultaneously has a significant effect on business development in Batam City